SPATIAL ANALYSIS OF THE EFFECT OF LAND COVER CHANGES ON THE SOCIO-ECONOMIC POPULATION IN PARAKANSALAK DISTRICT, SUKABUMI REGENCY - Taqyudin, Taqyudin; Efendi, Chairun Nisa; Supriatna, Supriatna; Restuti, Ratri Candra (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2021)
Many land changes have occurred in Indonesia, especially in developing areas, so those rural areas can turn into urban areas. These changes can be felt directly by the community and have an impact on the social economy of the surrounding population. The importance of knowing the social and economic conditions of the community to know the conditions of regional development. Therefore, this study aims to determine changes in land cover in 2014-2020 and their effect on the social economy of the population in Parakansalak District. This research uses a descriptive quantitative method with spatial and statistical analysis in it. The techniques used in data collection were questionnaires, interviews, and observations, while the data processing techniques used the Google Earth Engine platform, ArcGIS software, Excel, and SPSS. The results of the study showed that changes in land cover partially affected the socio-economic status of 51%, with the most affected being jobs and incomes of residents in the Parakansalak District. Employment is affected by 68% and income is affected by 71% of land cover changes. The land cover that changed the most was agricultural land in Bojonglongok Village and Parakansalak Village. Therefore, the occupations of the surrounding residents also changed, such as some residents becoming traders, landlords, ranchers, teachers, and so on, and eventually, it also affected their income.